Negative effects of acid rains on agricultural areas - Fatma Kunt; Ahmet Özkan (Annals of Environmental Science and Toxicology - Peertechz Publications, 2023)
Due to the atmospheric pollution loads that started with the industrial revolution and have increased exponentially in the process that has come to the present day, the natural components of the atmosphere have been damaged and changed. One of the negative return points of this human-made degradation in the natural order is acid rain. Acid rains harm people directly and/or indirectly. One of the indirect effects is the negative effects on the food chain. Acid rains affect agricultural products, however, they affect the products from the soil. As a result, agricultural fields and agricultural products are damaged. The decreasing resources (water, etc.) with global warming and climate change also increase the negative impact on agricultural products. In this study, the negative effects of acid rain on agricultural areas were investigated and it was aimed to put forward the measures to reduce these negative effects.